PENGARUH DAN RELEVANSI GUSJIGANG BAGI PERADABAN ISLAM DI KUDUS - Nur, Dany Miftah; Farohi, Ahmad (Program Studi Tadris IPS Fakultas tarbiyah IAIN Kudus, 2019)
Sayyid Ja'far Sodiq or known as Sunan Kudus is a figure who has an important role in the entry of Islam in Kudus. The multicultural Holy Society has a unique typology in morals, science and economics, known as